Increasing Independence in Hypertension at the Jannati Home for the Elderly, Gorontalo City - Andi Nuraina Sudirman; Haslinda Damansyah; Gunardi Pakaya; Ferawati Aridi; Nun’ Ain Pango (Pusat Studi Pembangunan dan Pemberdayaan, 2021)
Hypertension can be defined as persistent blood pressure where the systolic pressure is above 140 mmHg and the diastolic pressure is above 90 mmHg. In the elderly population, the elderly here are a group of people or people who are old, they carry out religious activities carried out by themselves and others. Independence in the elderly includes the ability of the elderly to carry out daily activities such as: bathing, dressing neatly, going to the toilet, changing places. , can control urination and defecation, and can eat alone. Independence refers to psychosocial abilities which include freedom to act, not depending on other people's abilities, not being influenced by the environment, and free to regulate their own needs.